Stories and stats: a mixed methods study of staff and male prisoner patient experiences of prison based mental health services - Hancock, Kate (Curtin University, 2009)
One consequence of the deinstitutionalisation of psychiatric care and increase in community care is the rising number of mentally ill people in prison populations where there are insufficient mental health professionals and services to address the treatment and rehabilitation needs of psychiatrically unwell prisoner patients. People with mental illness are over-represented in prison populations, and the provision of mental health services is a difficult task in an environment where discipline and safety take precedence over health treatment. This research investigated attitudes, perceptions, and experiences of prisoners, health professionals, and correctional staff in relation to mental illness and mental health service provison across eight prisons in Western Australia. The research aimed to gain a deeper understanding of experiences within prisons. Perceptions, attitudes and experiences of participants were explored using a mixed methods approach; both qualitative and quantitative methods were employed to gather information in a ‘two phase sequential design’ (QUAL/QUAN) (Creswell and Plano Clark 2007). The Phase One key informant interviews (n=17), and the key themes identified in the literature review, informed the development of the Phase Two quantitative survey questionnaires (n=168). These Phases acted as two different ways of exploring the research questions.One consequence of the deinstitutionalisation of psychiatric care and increase in community care is the rising number of mentally ill people in prison populations where there are insufficient mental health professionals and services to address the treatment and rehabilitation needs of psychiatrically unwell prisoner patients. People with mental illness are over-represented in prison populations, and the provision of mental health services is a difficult task in an environment where discipline and safety take precedence over health treatment. This research investigated attitudes, perceptions, and experiences of prisoners, health professionals, and correctional staff in relation to mental illness and mental health service provison across eight prisons in Western Australia. The research aimed to gain a deeper understanding of experiences within prisons. Perceptions, attitudes and experiences of participants were explored using a mixed methods approach; both qualitative and quantitative methods were employed to gather information in a ‘two phase sequential design’ (QUAL/QUAN) (Creswell and Plano Clark 2007). The Phase One key informant interviews (n=17), and the key themes identified in the literature review, informed the development of the Phase Two quantitative survey questionnaires (n=168). These Phases acted as two different ways of exploring the research questions.